WILL THE TRADITIONAL MEDICINE UN-PAUSE THE WORLD AND DECIDE THE FATE OF COVID-19? - S. K., JANANI; S. P., DHANABAL; R., SURESHKUMAR; KARTHIKA, CHENMALA; UPADHYAYULA, SAI SURYA NIKITHA (International Journal of Applied Pharmaceutics, 2021)
COVID-19 is a life-threatening disease that mainly affects the human respiratory system. In today’s world, scientists are working conscientiously for the identification of promising drugs and vaccines. But, when we look back to the former times, herbal medicines were considered for curing most of the diseases; luckily, nowadays, natural remedies are being carried forward by few researchers even for the treatment of most life-threatening diseases like cancer, diabetes and alzheimer’s etc. So, why can't we attempt the herbal formulation for the management of COVID-19 too? Since there is no proper scientific validation for traditional herbs and spices; it just can’t be simply ignored. When a product with less or few side effects can be prepared and made available for the benefit of people, there is nothing wrong in pondering them. Thus, keeping these points in mind, in this article, we have discussed about SARS CoV-2, their treatment options and the impact of natural remedies on both the former as well as novel coronavirus. Further, we have also emphasized on traditional Chinese medicine, various flavonoids and kabasura kudineer and their impact on coronavirus infection. Till now, there is no particular drug or vaccine available for the treatment of COVID-19; thus prevention is the only option. But, we hope that thorough study; screening, preclinical and clinical evaluation of natural compounds may give some action against SARS CoV-2. Moreover, incorporating natural herbs and spices in our diet can help in boosting immunity and fight against various life-threatening diseases.